Isolation and Physicochemical Characterization of Assam Bora Rice Starch for Use as a Plasma Volume Expander - Zaki Ahmad, Mohammad; Bhattacharya, Ashokanshu (Current Drug Delivery, 2010)
Water soluble polysaccharides are the most effective oncotic agents, which are used for the treatment of intravascular volume deficiency. Nowadays, they are used as basic material for plasma volume expander. Plasma volume expander based on starch has lower tendency to remain in any major organ of body in comparison to other plasma volume expander. Branched component of starch amylopectin is very similar in structure to glycogen, the reserve polysaccharides of animal; for all this reason starch is compatible with body tissues. Physicochemical properties of raw starch and amylopectin, isolated from Assam Bora rice were characterized for using it as plasma volume expander. Characterization involves the determination of ash value, weight average molecular mass, viscosity and resistance towards enzymatic (amylase) hydrolysis. Amylose content was almost negligible. The X-ray diffraction pattern of Assam Bora rice starch was typically A type. High degree of crystallinity of Assam Bora rice starch reflect its resistance towards enzymatic hydrolysis, which is of therapeutic advantage for using it as a plasma volume expander.
Keywords: degree of crystallinity